X-Ray Induced Formation of γ-H2AX Foci after Full-Field Digital Mammography and Digital Breast-Tomosynthesis - Schwab, Siegfried; Brand, Michael; Schlude, Ina-Kristin; Wüst, Wolfgang; Meier-Meitinger, Martina; Distel, Luitpold; Schulz-Wendtland, Rüdiger; Uder, Michael; Uder, Michael; Kuefner, Michael A. (PLoS ONE, 2013)
Purpose:To determine in-vivo formation of x-ray induced γ-H2AX foci in systemic blood lymphocytes of patients undergoing full-field digital mammography (FFDM) and to estimate foci after FFDM and digital breast-tomosynthesis (DBT) using a biological phantom model.Materials and Methods:The study complies with the Declaration of Helsinki and was performed following approval by the ethic committee of the University of Erlangen-Nuremberg. Written informed consent was obtained from every patient. For in-vivo tests, systemic blood lymphocytes were obtained from 20 patients before and after FFDM. In order to compare in-vivo post-exposure with pre-exposure foci levels, the Wilcoxon matched pairs test was used. For in-vitro experiments, isolated blood lymphocytes from healthy volunteers were irradiated at skin and glandular level of a porcine breast using FFDM and DBT. Cells were stained against the phosphorylated histone variant γ-H2AX, and foci representing distinct DNA damages were quantified.Results:Median in-vivo foci level/cell was 0.086 (range 0.067-0.116) before and 0.094 (0.076-0.126) after FFDM (p = 0.0004). In the in-vitro model, the median x-ray induced foci level/cell after FFDM was 0.120 (range 0.086-0.140) at skin level and 0.035 (range 0.030-0.050) at glandular level. After DBT, the median x-ray induced foci level/cell was 0.061 (range 0.040-0.081) at skin level and 0.015 (range 0.006-0.020) at glandular level.Conclusion:In patients, mammography induces a slight but significant increase of γ-H2AX foci in systemic blood lymphocytes. The introduced biological phantom model is suitable for the estimation of x-ray induced DNA damages in breast tissue in different breast imaging techniques. © 2013 Schwab et al.
CRIS-Team Scopus Importer:2023-03-08